Immune Checkpoint Protein Expression Defines the Prognosis of Advanced Thyroid Carcinoma - Luo, Yi; Yang, Yi-Chen; Shen, Cen-Kai; Ma, Ben; Xu, Wei-Bo; Wang, Qi-Feng; Zhang, Yan; Liao, Tian; Wei, Wen-Jun; Wang, Yu (Frontiers in Endocrinology, 2022)
Abstract Background: Patients with advanced thyroid carcinoma (TC), such as anaplastic thyroid carcinoma (ATC), poorly differentiated thyroid carcinoma (PDTC), and locally advanced papillary thyroid carcinoma (PTC), have poor prognoses and require novel treatments. Immune checkpoint inhibiters have shown heartening outcomes. However, they are largely unclear in advanced TCs. Thus, we demonstrated immune checkpoints (ICPs) profiles and investigated their potential clinical significance. Methods: A total of 234 TC patients were involved, with 22 ATCs, 44 PDTCs, and 168 PTCs, including 58 advanced PTCs. Immunohistochemistry was performed to evaluate nine ICPs (PDL1, PD1, CTLA4, BTLA, TIGIT, LAG3, VISTA, B7H3, and TIM3) expression via tissue microarrays (TMAs), and clinical correlations were analyzed simultaneously. Results: ATC had the highest positive rate of ICPs among the three pathological types, as well as relatively high ICP co-expression. ATC with high expression of PDL1 positivity had a poor prognosis. Shorter survival was associated with VISTA, B7H3, TIM3, and TIGIT expression in PDTC. The greater the co-expression of these four ICPs, the poorer the prognosis in PDTC patients. VISTA and B7H3 were the two most commonly expressed ICPs in advanced PTC, both of which were linked to a poor prognosis. Conclusions: PDL1 is linked to the OS of ATC. A subset of PDTC is likely immunogenic with poor prognosis and co-expression of VISTA, B7H3, TIM3, and TIGIT. Further, VISTA and B7H3 are prognostic biomarkers in advanced PTC. Single or combined blockade targeting these ICPs might be effective for advanced TCs in the future.